The institutional characteristics of soccer in Germany: A qualitative interview study - Kasano, H. (Japan Journal of Physical Education, Health and Sport Sciences, 2022)
The purpose of this study was to clarify the institutional characteristics of soccer in Germany from the viewpoint of the German Football Association (DFB), utilizing as a theoretical framework the subjective theory of sport organization, based on the results of interviews with the DFB and a German soccer coach. Using this approach, we hoped to provide a multifaceted perspective on the institutional characteristics of organizing enthusiasts. The present analysis was able to clarify the institutional characteristics of soccer in Germany from the perspective of the sport organization. It was suggested that the institutional characteristics were supported by the "Sport Ideology" of the DFB and that these formed the social character of the enthusiasts. Then, by systematizing its social character, a cyclical structure in which it became the "Sport Ideology" of the DFB was demonstrated.